1990
DOI: 10.1002/chin.199019001
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Vibrational Spectroscopy of the Hydrated Hydronium Cluster Ions H3O+·(H2O)n (n = 1, 2, 3).

Abstract: ChemInform Abstract Using a new spectroscopic method, the gas phase IR spectra of the title cluster ions, produced in a high pressure corona discharge source, are observed between 3550 and 3800 cm-1. The spectroscopic method is a two color laser scheme consisting of a tunable cw IR laser with 0.5 cm-1 resolution used to excite the O-H stretching vibrations and a cw CO2 laser that dissociates the vibrationally excited cluster ion through a multiphoton process. The dissociation products are detected by combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…With these issues in mind, it seems that the strongest argument in favor of an Eigen isomer is based on the relative cluster energetics. “The n = 4 complex is expected to be the classic “Eigen” ion, having a central hydronium surrounded symmetrically by three water molecules each hydrogen bonded to a single OH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these issues in mind, it seems that the strongest argument in favor of an Eigen isomer is based on the relative cluster energetics. “The n = 4 complex is expected to be the classic “Eigen” ion, having a central hydronium surrounded symmetrically by three water molecules each hydrogen bonded to a single OH.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of aqueous acid solutions has been a subject of intense debates on whether the dominant protonated water structure is H 3 O + ·(H 2 O) 3 (the “Eigen cation”) , or H 2 O···H + ···OH 2 (the “Zundel cation”). ,,, It therefore seemed reassuring that for gas-phase clusters there was a consensus, the protonated water tetramer being an Eigen cation (Scheme left), which is the most stable isomer. Its measured infrared (IR) spectrum showed several characteristic bands, of which four were reproduced theoretically [the water symmetric stretch ( ss ) and asymmetric stretch ( as ) modes near 3700 cm –1 , a strong hydrogen-bonded (HBed) OH band at 2665 cm –1 , and the free bend ( b ), 1615 cm –1 ]. This, however, left two prominent bands unassigned (at 1750 and 1050 cm –1 ), and a few smaller peaks (1847, 1904, 2307 and the “α band” at 2245 cm –1 ), which are thought to be combination bands …”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, stability of magic numbered water clusters was first reported by Lin in 1973 . Later, Yeh et al and Jiang et al explained the structure of the magic cluster in detail through IR–spectroscopic technique. They have concluded that the geometry change from 1D chain to 2D net structure occurs at around n = 10 and transition to 3D structure completed at around n = 21, which has been reported as the first magic cluster.…”
Section: Introductionmentioning
confidence: 94%
“…The study of the proton transfer mechanism in water is an important area of investigation. Advances in experimental techniques have allowed for the study of this mechanism in bulk systems, , the air/water interface, nanodroplets and reverse micelles, , and gas-phase water clusters. Cold, protonated water clusters provide model systems through which one can experimentally and theoretically interrogate the underlying physics of an excess proton in a known environment. In particular, vibrational spectroscopy of these systems allows for the direct interrogation of the motions that underpin proton transfer.…”
Section: Introductionmentioning
confidence: 99%